2015
DOI: 10.1007/978-3-319-20609-7_17
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Pronunciation Error Detection and Feedback Generation for CALL Applications

Abstract: This paper describes a new method of automatic error detection in Computer Assisted Language Learning (CAPT) system. The method combines linguistic knowledge and modern speech technology. Our HMM classifier trained from annotations of linguists is not only capable of classifying correct and wrong phonemes, but also can tell how wrong an error phoneme is pronounced. Phone errors in L2's speech, like phoneme substitution or distortion are detected with high accuracy, and at the same time, corrective feedback wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Previous research (Singh and Harun 2020;Alyammahi et al 2021) has shown that clear and concise communication can lead to an increase in productivity, efficiency, and understanding in the workplace. Increasingly, organizations are using automated speech scoring techniques to screen job candidates as well as to provide computer-assisted language learning (CALL) (Ai 2015). Typically, speech scoring systems comprise measurements of different competencies including Pronunciation, Fluency, Automatic Listening, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research (Singh and Harun 2020;Alyammahi et al 2021) has shown that clear and concise communication can lead to an increase in productivity, efficiency, and understanding in the workplace. Increasingly, organizations are using automated speech scoring techniques to screen job candidates as well as to provide computer-assisted language learning (CALL) (Ai 2015). Typically, speech scoring systems comprise measurements of different competencies including Pronunciation, Fluency, Automatic Listening, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in automated speech scoring (Witt and Young 1997;Ai 2015;Evanini and Wang 2013) have examined phone level scores derived from GMM-HMM (Gaussian Mixture Model − Hidden Markov Model) based speech recognizer outputs. With the proliferation of deep learning techniques, more recent studies (Ying 2019;Hu et al 2015;Sudhakara et al 2019) have used acoustic models trained using a Deep Neural Network to improve mispronunciation detection & diagnosis (MDD).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to help people practice and improve their pronunciation skills [6][7][8]. CAPT consists of two components: an automated pronunciation evaluation component [9][10][11] and a feedback component [12]. The automated pronunciation evaluation component is responsible for detecting pronunciation errors in spoken speech, for example, for detecting words pronounced incorrectly by the speaker.…”
Section: Introductionmentioning
confidence: 99%